Exploiting drought tolerance traits and genetic diversity of synthetic hexaploid wheat in winter wheat breeding - Becker, Steven Richard, author; Byrne, Patrick F., advisor; Bauerle, William L., committee member; Haley, Scott D., committee member; McKay, John K., committee member (Colorado State University. Libraries, 2014)
As the world's most widely dispersed food crop, wheat (Triticum spp.) is produced on approximately 22% of currently cultivated land. This wide distribution of environments and the large demand for consumption requires the adaptability of wheat to various environmental stresses. Therefore, this study was conducted to assess the benefits of introgressing synthetic hexaploid wheat (SHW) diversity into winter wheat in the U.S. Great Plains. The objectives of this study were to: 1) identify differences in drought tolerance-related physiological and morphological trait expression among SHW lines and adapted winter wheat cultivars; 2) evaluate and select SHW-derived backcross lines from multi-environment field studies for potential use as breeding germplasm; and 3) locate genomic regions of synthetic origin that show promise for yield improvements through targeted introgression into elite bread wheat backgrounds. The instability of crop yields is predicted to increase due to climate change and environmental stresses, with drought considered the abiotic stress that is most associated with a loss of yield in cereal crops. The improvement of yield and drought stress tolerance in bread wheat (Triticum aestivum L.) through the introgression of novel alleles from ancestral species may be feasible. Synthetic hexaploid wheat, which incorporates the AABB genome from Durum wheat and the DD genome from the progenitor Aegilops tauschii, has shown promise for improving bread wheat yield and agronomic performance. In this study a group of six SHW lines were selected from a collection of 412 lines developed by the International Maize and Wheat Improvement Center (CIMMYT, El Batan, Mexico). A subset of SHW lines was selected after two years of testing for visual agronomic traits and yield in Colorado. The six SHW lines were analyzed in greenhouse conditions for differences in drought tolerance traits relative to four adapted cultivars. This experiment focused on root morphology traits of these genotypes grown in one meter tall plastic tubes. Some synthetic lines ranked better than the adapted check varieties under greenhouse conditions for drought tolerance traits such as deep root biomass, longest root, and stomatal density. The plasticity of total root biomass and root biomass in the deepest third of the tubes was also found to be significantly correlated (P<0.05, r = 0.72 and 0.70, respectively) with a calculated drought index. Digital analysis of root length in five root diameter classes indicated a significant (P<0.05) increase of small diameter root growth under drought stress for drought tolerant genotypes compared to drought sensitive genotypes. The development and testing of 10 SHW-derived BC1F1:2 populations (15 lines per population), with 'Hatcher' and 'Goodstreak' as the recurrent parents, identified six out of twelve SHW populations that showed the highest overall yield in eight Colorado and Nebraska environments in 2009-2010 and 2010-2011. Single plant selections were made from the highest yielding SHW-derived lines within each selected population and planted as headrows in 2011-2012. The top 10% of the headrows was selected based on visual assessment of yield potential and agronomic attributes such as early maturity date and lodging and disease resistance. Advanced yield testing of the selected fraction was then conducted in 2012-2013. Synthetic-derived lines with Hatcher as a recurrent parent showed a wide variety of yield under both irrigated and rainfed conditions in the summer of 2013. Two SHW-derived lines outranked Hatcher for grain yield in all three environments in 2013 with two additional lines ranking higher than all adapted check cultivars in both irrigated and rainfed environments. Of several agronomic traits evaluated, harvest index and canopy temperature showed the highest correlations with grain yield under drought (r = 0.55 and -0.53, respectively, P<0.05). Canopy temperature was also assessed every other hour (0900 to 1730 h) for a single day during the grain fill period. This analysis identified high yielding SHW-derived lines showing contrasting responses (both continuous and variable period of low canopy temperature) relative to Hatcher under drought. Genotyping-by-sequencing data for the SHW-derived lines identified 13 single nucleotide polymorphisms which showed a preferential selection for the allele of synthetic origin after three selection events for improved grain yield. Our results demonstrate improvements in yield and agronomic performance in SHW-derived lines. Therefore we conclude that the use of SHW has good potential for introgression of diversity into elite winter bread wheat in the U.S. Great Plains.
Keywords: drought tolerance; genetic diversity; genotyping-by-sequencing; synthetic hexaploid wheat; trait introgression; winter wheat breeding